Tolerância de Diferentes Cultivares de Cana-de-Açúcar (Saccharum spp.) a Herbicidas - Zera, F. S.; Azania, C. A.M.; Schiavetto, A. R. [UNESP]; Lorenzato, C. M.; Azania, A. A.P.M. (FapUNIFESP (SciELO), 2011)
This work aimed to evaluate the tolerance of sugarcane cultivars to sulfentrazone, imazapic, isoxaflutole, clomazone and ametryn + trifloxysulfuron-sodium. The experiment was arranged in a randomized block design in a split-plot scheme. The cultivars were allocated to the plots and the herbicides to the sub-plots (five 8.0 m long rows and 1.5 m spacing, with 4 repetitions. The herbicides sulfentrazone (0.8 kg ha -1), imazapic (0.147 kg ha -1), isoxaflutole (0.1125 kg ha -1), clomazone (1.1 kg ha -1), ametryn (1.463 kg ha -1) + trifloxysulfuron sodium (0.037 kg ha -1) and control were evaluated on 3-yr-old ratoons of the cultivars IACSP94-2094, IACSP94-2101, IACSP93-3046, IACSP94-4004, IAC86-2480 and RB72454 in post emergence. The traits evaluated were: plant toxicity symptoms in the plant leaves; total chlorophyll content and photochemical efficiency (Fv/Fm) at 15, 30 and 60 days after application (DAA); height (cm) at 30 and 270 DAA, and plant stand (stalk m-1) at 30 and 180 DAA. Diameter (cm), estimated productivity (t ha -1) and quality analysis were evaluated at 270 DAA. The sugarcane cultivars IACSP94-2094, IACSP93-3046, IACSP94-4004, IAC86-2480, RB72454, and IACSP94-2101 especially, were susceptible to clomazone up to 30 DAA, due to leaf chlorosis and lower chlorophyll content, but had no effect on quality characteristics and productivity. The cultivars were also tolerant to other herbicides.
Tolerance of different sugarcane (Saccharum spp.) cultivars to herbicides
Keywords: Control; Plant toxicity; Selectivity